Malignant breast phyllodes tumor in pregnancy – a case report - Pytel, Jacek; Dedecjus, Marek; Naze, Maciej; Stróżyk, Grzegorz; Brzeziński, Jan (Menopause Review/Przegląd Menopauzalny, 2009)
Phyllodes tumor occurred in 0.2-1% all breast tumors, predominant in 35-55 years old women, unilateral. It can growth very fast and received big size. Usually is benign but malignant form with metastases are described. Also conversion benign to malignant form occurred. There are very few reports concerning the presence of malignant form phyllodes tumor in breast of pregnant women. 25 years old women discovered small lump in her left breast. Ultrasound and needle biopsy was done without any malignancy. She refused treatment. Two years later, in 20th week of pregnancy, tumor was rapidly growing. Ultrasound and needle biopsy gave result of phyllodes tumor malignant form. Simple mastectomy was done. There is a lack of information in literature abut malignant form of phyllodes tumor associated with pregnancy.